Literature Review: Food Processing in Minimizing Chemical Contamination of Rhodamin B in Shrimp Paste and Chlorpirifos Residue in Fresh Vegetables Garnish Which are Circulating in the Communities in Indonesia - Nuur Anisa Aprilianintyas (Universitas Airlangga, 2020)
Introduction: Food circulation among communities is prone to chemical contamination. The contamination is obtained from both food processing and food cultivation (planting, raw materials). One of the examples related to chemical contamination can be seen in the contamination of rhodamine B on Terasi. Although there is a prohibition on using Rhodamine B compounds in food add-ons, which is listed in Regulation of Ministry of Health of Republic Indonesia No.722/Menkes/Per/IX/1988, its usage is widely found. Similarly, chlorpyrifos pesticide residue in lalapan is the other example provided. The usage of it remains to continue even though the result of pesticide residue value is under BMR SNI 7313:2008. The article aims to study food processing efforts in minimizing the chemical contamination of Rhodamine B in shrimp terasi and chlorpyrifos residue in the lalapan vegetables in the communities in Indonesia. A literature review on scientific publications was undertaken through Google Scholar, ResearchGate, Neliti, ScienceDirect, LIPI, Directory Open Acces Journal, and Crossref. The keywords used were related to rhodamin B on terasi, synthetic dyes on terasi, natural dyes for terasi, vegetable pesticide residues, Chlorpyrifos residue on vegetables, and how to reduce chlorpyrifos residue in vegetables. All of them were published between the 2015 – 2020 period. Discussion: Chlorpyrifos residue in vegetables can be reduced by washing, soaking brine, and boiling. The usage of rhodamine B on Terasi can be replaced by the application of dragon fruit skin extract and angkak (red yeast rice) for natural dye alternatives. Conclusion: Washing food with running water and soaking it in hot water before food consumption can lower chlorpyrifos residue level in dark vegetables. However, it is more significant to lover the residue level through the boiling step. The use of natural pesticides can be used as the choice of alternative. Moreover, rhodamine B on terasi can be replaced with natural dye alternatives such as angkak (red yeast rice) and dragon fruit skin extract.